Kepemimpinan Visioner dalam Menentukan Arah Kebijakan Pemerintah - Asih Widi Lestari; Febianus Angga Saputra; Firman Firdausi (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2023)
Making a policy is determined by a leader who is in the institution and the leader has a leadership style, the leadership style that is owned will affect the final result of the policy to be issued. This study aims to find out how a leader applies the visionary leadership style in determining a policy and what are the factors that influence policy making in Sidomulyo Village Government, Batu District, Batu City by using qualitative methods. The application of data collection techniques in this study used interview, observation and documentation techniques. The results of this study, a leader who applies a visionary leadership style in his area of authority will have the right future plans and have been arranged regularly through predetermined processes. The visionary leadership style that is applied keeps the village moving forward and developing in a good direction through well-organized development planning, community participation in events organized by the village and community empowerment in an effort to increase human resources. visionary leadership in sidomulyo village has been going well and in making policies the village head will always consider based on the needs of the community.